Simply the best, better than all the rest? Validity issues in selections in elite sport - Johansson, A.; Fahlén, J. (International Journal of Sports Science & Coaching, 2017)
Selecting the 'right' athletes to competitions and games is crucial in eventually deciding winners and champions. Thus, the purpose of this study was to discuss selections to top-level sport teams using validity concepts as theoretical points of departure. Drawing on data from 14 semi-structured interviews with elite coaches (selectors) in football (n = 8) and alpine skiing (n = 6), this article adds to the knowledge on rationales behind selection decisions in elite sport, how selections are performed and with what consequences. Results point to several key validity concerns in selection processes such as the (non) use of explicit selection criteria, lack of structure in selection processes and coaches' giving way to gut feelings and their 'eyes for the sport' instead of utilizing various selection aids at hand. ABSTRACT FROM AUTHOR